Parenting During the Elementary School Years, Part 1: Preventing Misbehavior - Millie Ferrer; Anne M. Fugate; Ingrid Rivera (EDIS, 2002)
This document is FCS2202, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 10, 2002. Updated July 2003.